Temporal and spatial dynamics of human immunodeficiency virus type 1 circulating recombinant forms 08BC and 07BC in Asia - Tee, K.K.; Pybus, O.G.; Li, X.J.; Han, X.X.; Shang, H.; Kamarulzaman, A.; Takebe, Y. (2008)
Human immunodeficiency virus type 1 (HIV-1) CRF08BC and CRF07BC are two major recombinants descended from subtypes B ' and C. Despite their massive epidemic impact in China, their migration patterns and divergence times remain unknown. Phylogenetic and population genetic analyses were performed on 228 HIV-1 sequences representing CRF08BC, CRF07BC, and subtype C strains from different locations across China, India, and Myanmar. Genome-specific rates of evolution and divergence times were estimated using a Bayesian Markov chain Monte Carlo framework under various evolutionary models. CRF08BC originated in 1990.3 (95 credible region CR, 1988.6 to 1991.9) in Yunnan province before spreading to Guangxi (south) and Liaoning (northeast) around 1995. Inside Guangxi region, the eastward expansion of CRF08_BC continued from Baise city (west) to Binyang (central) between 1997 and 1998 and later spread into Pingxiang around 1999 in the south, mainly through injecting drug users. Additionally, CRF07_BC diverged from its common ancestor in 1993.3 (95% CR, 1991.2 to 1995.2) before crossing the border into southern Taiwan in late 1990s. Phylogenetic analysis indicates that both CRF08_BC and CRF07_BC can trace their origins to Yunnan. The parental Indian subtype C lineage likely entered China around 1981.2 (95% CR, 1976.7 to 1985.9). Using a multiple unlinked locus model, we also showed that the dates of divergence calculated in this study may not be significantly affected by intrasubtype recombination among different lineages. This is the first phylodynamic study depicting the spatiotemporal dynamics of HIV/AIDS in East Asia.